Perancangan Alat Pengendali Pompa Air Berbasis IOT - Nur Fauziah; Nuris Dwi Setiawan; Danang Danang; Eko Siswanto (Asosiasi Riset Ilmu Teknik Indonesia, 2023)
Of course, a soccer field needs water and the fertility of the field soil so that the grass can grow. The development of science and technology currently has a big influence on getting work done. A pump is a tool used to move liquids (fluids) from one place to another through pipes (channels) by adding energy to the fluid being moved and continuing continuously. Currently, many water pumps still use the manual method, namely using a switch or even just using a plug. Grass will also live if the soil has appropriate humidity, if the soil moisture level is low, the grass will die if there is excess moisture and it will not be able to grow. This problem certainly requires a solution that can help monitor soil moisture as well as control water pumps. By utilizing NodeMCU ESP8266 microcontroller technology as the control center, the YL-69 sensor measures soil moisture values ​​and also relays as a replacement for manual switches. To control pump conditions via Blynk.